Uma proposta de ensino de eletrostática no ensino médio auxiliado por ferramentas computacionais - Melo, Cicero David Pereira de (Universidade Federal Rural do Semi-Árido, 2018)
A strong tendency demonstrated in the studies of the subject in question is the use of the digital technologies of information and communication (TDICs) as tools of support in the process of teaching and learning. The present work aims to analyze the potential of the use of computational tools (simulations and graphing tools) in the teaching of electrostatics. For this, the educational product was constructed aiming at didactic sequences, based on the theory of Significant Learning of David Ausubel, from the PhET Loads and Fields simulation of the University of Colorado. Also, as part of the Product, the material to support the Physics teacher was developed, aiming at the repetition of the activities developed in this research or the elaboration of new activities. The product was applied in E.E.M. Governor Adauto Bezerra de Iguatu-CE, with high school students. The learning outcomes obtained through the pre-test and post-test analysis suggest the effectiveness of the Educational Product, which may lead to the conclusion that the use of TDICs in line with the use of Conceptual Maps in the teaching of Electrostatics demonstrates considerable potentiality
Keywords: Eletrostática; TDIC; Cargas; Electrostatics; DICT; Loads; Campos; Fields; CIENCIAS EXATAS E DA TERRA::FISICA